Konkubinat a bezpodstawne wzbogacenie (uwagi na tle judykatury Sądu Najwyższego) - Szlęzak, Andrzej (Wydział Prawa i Administracji UAM, 1989)
The author criticizes the view expressed by the Supreme Court that in cases of cohabitation without marriage there is no room for all types of condictions (condictio indebiti, condictio sine causa, condictio causa data causa non secuta, condictio causa finita) may arise between the cohabiting partners. He also criticizes the application of the construction of „obligation de conscience" to claims raised by informal spouses, indicating that the above construction of the French civil law is incompatible with the Polish civil law provisions. In particular, the notion of „obligation de conscience" obscures the distinction between legal and moral norms and makes it difficult to arrive at a plausible interpretation of Art. 411 sec. 2 of the Civil Code on imperfect obligations.
Cohabitation without marriage and unjustified enrichment. Remarks in the light of the supreme court decisions